2005
DOI: 10.1016/j.neuropharm.2005.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Short-term steroid treatment increases δ GABAA receptor subunit expression in rat CA1 hippocampus: Pharmacological and behavioral effects

Abstract: In this study, 48 h administration of 3α-OH-5β-pregnan-20-one (3α,5β-THP) or 17β-estradiol (E 2 )+progesterone (P) to female rats increased expression of the δ subunit of the GABA A receptor (GABAR) in CA1 hippocampus. Coexpression of α4 and δ subunits was suggested by an increased response of isolated pyramidal cells to the GABA agonist 4,5,6,7-tetrahydroisoxazolo[5,4-c]pyridin-3-ol (THIP), following 48 h steroid treatment, and nearly complete blockade by 300 μM lanthanum (La 3+ ). Because α4βδ GABAR are extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
119
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 148 publications
(127 citation statements)
references
References 62 publications
8
119
0
Order By: Relevance
“…Preclinical studies indicate that the impact of neurosteroids on the GABA receptor is mediated by changes in their levels rather than their absolute concentration. Both increases and decreases in progesterone metabolite neurosteroids induce changes in the alpha 4 subunit conformation of the GABA A R sufficient to produce anxiety-like behaviors (Gulinello et al, 2001;Gulinello and Smith, 2003;Shen et al, 2005). Thus, it is possible that effects of progesterone to precipitate PMDD symptoms (Schmidt et al, 1998) could be mediated by changes in allopregnanolone and/or an abnormal conversion of progesterone to its neurosteroid metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies indicate that the impact of neurosteroids on the GABA receptor is mediated by changes in their levels rather than their absolute concentration. Both increases and decreases in progesterone metabolite neurosteroids induce changes in the alpha 4 subunit conformation of the GABA A R sufficient to produce anxiety-like behaviors (Gulinello et al, 2001;Gulinello and Smith, 2003;Shen et al, 2005). Thus, it is possible that effects of progesterone to precipitate PMDD symptoms (Schmidt et al, 1998) could be mediated by changes in allopregnanolone and/or an abnormal conversion of progesterone to its neurosteroid metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, our earlier studies have demonstrated that 48 h THP administration also increases anxiety in female rats (Gulinello et al, 2001), an effect closely correlated with increased expression of α4 and δ GABAR subunits (Shen et al, 2005). Interestingly, one study reported increased responsiveness to low concentrations of ethanol in women with PMDD (Sundstrom et al, 1998), although a second study (Nyberg et al, 2004a) by the same group found this increased sensitivity to be nonsignificant due to variability in response.…”
Section: Discussionmentioning
confidence: 94%
“…Our previous work demonstrated that 48 h THP administration paradigm increases expression of both the α4 and δ GABAR subunits in CA1 hippocampus (Shen et al, 2005). Coexpression of α4 and δ subunits was suggested (Shen et al, 2005) by pharmacological findings demonstrating an increased response to the GABA agonist gaboxadol and inhibitory effects of the trivalent cation, La 3+ on CA1 pyramidal cells, acutely isolated or recorded in the slice. These findings are characteristic of increased expression of α4βδ GABAR, for which gaboxadol produces a greater maximal current than GABA and which are nearly completely inhibited by La 3+ (Brown et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations